KOMPARASI ANALISIS KELAYAKAN USAHATANI PENANGKARAN BENIH PADI DAN USAHATANI PADI KONSUMSI DI PROVINSI SULAWESI TENGAH - Muhammad Iqbal; Muhammad Afif Juradi (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2015)
The existence of rice farming can be  generally  classified into two-category, namely rice farming for breeding and rice farming for consumption. This article aims at: (1) identifying and describing the rice farming; (2) analyzing the feasibility of rice farming for breeding and consumption; and (3) formulating the development policy of rice  farming  for  breeding  and  consumption  in  the  locale  of  the  study  (Central Sulawesi  province).  The  research  result  shows  that  the  extent  of  feasibility  of  rice farming  for  breeding  (RCR=1.80)  was  higher  than  that  of  rice  farming  for consumption (RCR=1.67). Even though the rice farming for breeding was prospective, the sustainability of this rice farming activity would be depended upon demand from farmers and other users, the existing government program, and financial investment capacity  of  rice  farmer  breeders.  Hence,  assuring  the  demand  and  providing  the favorable price of rice seeds are two important aspects supporting the continuity of  rice  farming  for  breeding  includes  rice  farming  for  consumption  in  the  province  of  Central Sulawesi.